Our experience with the love handle and its surroundings as a donor area of autologous fat grafting at the radiothreapy demaged breast (Annals of Medical Research, 2024)
Aim: Patients who had prior breast reconstruction using implants, subsequently underwent radiotherapy resulting in breast damage, and had received at least one session of fat injection were included in the study. This aim of this study was to determine the rationale behind selecting the “love handle” and its adjacent regions as the primary donor site for fat grafting in this patient group.Materials and Methods: This retrospective study included 86 patients who had undergone either nipple sparing or skin-sparing mastectomy between January 2019 - December 2023. The fat from each side was removed equally. The depressed areas within the fat removal site and patient satisfaction were assessed. The evaluation was performed at least 6 months after the last session.Results: The mean body mass index was 28.9 kg/m2. Of these patients, 26 (30%) underwent a single session, while 60 patients (70 %) received two or more sessions of fat injection. An average of 120 cc of pure fat graft was extracted from the “love handle” and its adjacent areas during the initial session. Except for one patient, all other patients reported that they were satisfied with the procedure.Conclusion: The ‘love handle’ and its surroundings is ideal for these patients due to its proximity to the breast, distance from vital vessels and nerves, ability to yield a sufficient amount of fat in the initial session, the ability for successive sessions as BMI increases, and low complication.
Keywords: Breast reconstruction; Fat injection; Radiation; Autologous fat graft; Nipple-sparing mastectomy; Direct-to-implant reconstruction